Portafolio management: A critical view beyond Markowitz Gestión de portafolios. Una mirada crítica más allá de Markowitz - Duván Darío Grajales Bedoya (AD-minister, 2009)
<span style="color: #666666; font-family: 'Trebuchet MS'; font-size: 12px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; background-color: #ffffff; display: inline !important; float: none;">Since its first appearance, the Markowitz model for portfolio selection has been a basic theoretical reference, opening several new development options. However, practically it has not been used among portfolio managers and investment analysts in spite of its success in the theoretical field. This paper presents and discusses the Markowitz’s model limitations modal to its practical implementation, the existence of transaction costs, equilibrium considerations, technical and fundamental analysis importance and the focus on behavioural finance as that of limited rationality, determine that the decision process of the individuals possesses limitations so much cognitive as computing that reduce perfection to their decisions, nevertheless, these theories of behavioural portfolios is possible to consider to be more a descriptive theory of how the investors construct their portfolios, in contrast with the theory of Markowitz's portfolios that is more prescriptive on having tried to instruct the investors how they must their portfolios. Desde su aparición, el modelo de Markowitz ha sido un referente teórico fundamental para la selección de carteras de valores y ha dado lugar a múltiples desarrollos y derivaciones. Su utilización en la práctica, entre gestores de carteras y analistas de inversiones, no es tan amplia como podría esperarse de su éxito teórico. Aquí se presentan y discuten sus limitaciones en cuanto a implementación práctica, presencia de costos de transacción, consideraciones de rebalanceo, importancia de los análisis fundamental y técnico, y el enfoque de finanzas del comportamiento que, como el de racionalidad limitada, determinan que el proceso de decisión de los individuos posee especificaciones cognitivas y computacionales que le restan perfección a las decisiones. Tales teorías de comportamiento se pueden considerar descriptivas de cómo los inversionistas construyen sus portafolios, en contraste con la de Markowitz, más prescriptiva, pues procura instruir a los inversionistas acerca de cómo deben configurar sus portafolios.